Exponential Sum Modeling of Reswick and Rogers Pressure-Duration Curve: A New Analysis and Model - Oscar A. Linares; Darko Stefanovski; Raymond C. Boston (Journal of Basic & Applied Sciences, 2012)
Reswick and Rogers model is not valid for predicting the effects of short- and long-time tissue exposures to contact pressures because it lacks intercepts. A different model, without those asymptotic properties, that could fit the shape of the curve well, could potentially provide useful information. We used modeling to test the hypotheses that an exponential model could fit Reswick and Rogers pressure-duration curve, and, if so, to determine the order of the best fit exponential model. Up to four exponential sum models were fit. Three exponentials provided the best fit [Weighted sum-of-squared residuals 72, Akaike Information Criterion 89, r=0.997]. Thereby identifying three homogeneously distinct anatomical pressure-load containing tissue compartments: skin, fat, and muscle. A fourth compartment, bone, could not be identified because of limited resolution of the data. Our results suggest that the fat pressure-load containing compartment may play an adaptive compensatory preventive role in response to pressure loads—“a cushion effect.” Exponential sum modeling of pressure-duration curves provides a new approach for studying the dynamics of compression in normal and disease states in humans, and it may be useful for practical application at the point-of-care to assist with prevention and treatment of pressure ulcers.